The Influence of Socio-Ecological Networks on Willingness to Communicate in English for Japanese People - Ito, Takehiko (Frontiers in Psychology, 2021)
This study investigates the effect of the socio-ecological network on the willingness to communicate in English among Japanese people. Previous studies have shown that relational mobility (socio-ecological factor), which is defined as the availability of opportunities to choose new relationship partners, positively affects the willingness to communicate in English for Japanese people. However, the network structure of relational mobility and its effects have not been revealed yet. The present study conducted network analysis with 474 Japanese university students and found the two clusters that correspond to the dimensions of relational mobility in the network. Three variables regarding opportunities to meet new people and leave current relationships positively affected the willingness to communicate in English; one had a negative effect. Centrality indices, such as nodes strength, betweenness, and closeness, revealed the centrality of several variables in the network. Bootstrapping methods showed the trustworthiness of the estimated network structure and centrality indices as well as edges and variables whose effects differed significantly from that of others. Contrary to the regression analysis results, the network analysis findings can help us understand the profound effect of relational mobility on the willingness to communicate in a second language, which will prove useful for intervention studies.